Massive Hemoptysis from Pulmonary Artery Aneurysms - A Kürşat Bozkurt (Canadian Respiratory Journal)
Aneurysms of the pulmonary arteries are rare. The author reports a case of a patient with bilateral pulmonary artery aneurysms, in whom the nature of the lesions was not known. Pulmonary artery aneurysms should be included in the differential diagnosis of lung masses.